(untitled) (Journal of Health, Population and Nutrition, 2009)
In Pakistan, the vital registration system is weak, and population-based data on the maternal mortality ratio are limited. This study was carried out to collect information on maternal deaths from different existing sources during the current year-2007 (prospective) and the past two years-2005 and 2006-(retrospective), identify gaps in information, and critically analyze maternal deaths at the community and health-facility levels in two districts in Pakistan. The verbal autopsy questionnaire was administered to households where a maternal death had occurred. No single source had complete data on maternal deaths. Risk factors identified among 128 deceased women were low socioeconomic status, illiteracy, low-earning jobs, parity, and bad obstetric history. These were similar to the findings of earlier studies. Half of the women did seek antenatal care, 34% having made more than four visits. Of the 104 women who died during or after delivery, 38% had delivered in a private facility and 18% in a government facility. The quality of services in both private and public sectors was inadequate. Sixty-nine percent of deaths occurred in the postpartum period, and 51% took place within 24 hours of delivery. The study identified gaps in reporting of maternal deaths and also provided profile of the dead women and the causes of death. Key words: Causes of death; Maternal mortality; Risk factors; Socioeconomic factors; Verbal autopsy; Pakistan doi: 10.3329/jhpn.v27i2.3329 J Health Popul Nutr 2009 April;27(2):170-183